2007
DOI: 10.1099/jmm.0.46765-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ability of Staphylococcus aureus isolates from bacteraemic patients with and without metastatic complications to invade vascular endothelial cells

Abstract: Invasion of vascular endothelial cells is thought to be a critical step in the development of metastatic infections in patients with Staphylococcus aureus bacteraemia. This study was designed to evaluate the association between the ability to invade endothelial cells and metastatic infection by S. aureus. Patients with metastatic infection were identified among those with community-acquired S. aureus bacteraemia in a tertiary referral hospital. Patients with simple bacteraemia caused by S. aureus over the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Park et al . investigated if any association was present between cytotoxicity of clinical S. aureus isolates and their abilities to cause metastatic infections . They found that the ability to induce host cell death and be cytotoxic to endothelial cells was not a major determinant of metastatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al . investigated if any association was present between cytotoxicity of clinical S. aureus isolates and their abilities to cause metastatic infections . They found that the ability to induce host cell death and be cytotoxic to endothelial cells was not a major determinant of metastatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the intracellular activity of radezolid against different strains of S. aureus with various resistance mechanisms, including to linezolid. Finally, we used different cell types as models of territories where S. aureus can survive intracellularly (endothelial cells, osteoblasts, respiratory epithelial cells, keratinocytes, and fibroblasts [11,14,22,36,41]), together with phagocytic cells (macrophages).…”
mentioning
confidence: 99%
“…Staphylococcal sepsis are in most cases accompanied by metastatic foci in various organ systems. Most commonly affected organs are the heart valves, bones and joints, lungs, kidneys, central nervous system, skin and soft tissue (12). The study of Fowler and colleagues (7) showed that, among other metastatic complications 89 patients had endocarditis 54 septic arthritis and meningitis 12.…”
Section: Discusionmentioning
confidence: 99%